Penataan Perizinan Dan Status Perkebunan Tanpa HGU di Sulawesi-Selatan - Tri Suhendra Arbani (El-Iqthisadi, 2020)
AbstractThis study examines two things, namely the status of state land granted to PTPN XIV, which has expired its HGU and licensing arrangements in the plantation sector, this research uses jurist normative research using a law editor and a conceptual approach. With regard to the PTPN XIV HGU, it is clear that the problems arose due to the unclear land status after the expiration of the HGU permit. From the perspective of the law, it is very clear that land that has expired its HGU is the obligation of PTPN XIV to return it to the state as the party that grants the permit. Improvement of the plantation licensing chain starting from location permits, forest area release permits, plantation business permits, cultivation plantation permits, processing plantation business permits, land clearing permits.Keywords: Business Use Rights, Licensing, Plantation. AbstrakPenelitian ini mengakaji bertujuan mengkaji dua hal yakni status lahan negara yang diberikan kepada PTPN XIV yang telah masa habis masa HGU nya dan penataan perizinan dibidang perkebunan, penelitian ini menggunakan penelitian normative yuris dengan menggunakan pendekan undang-undang dan pendekatan konseptual. Permasalahan tentang HGU PTPN XIV, sudah jelas bahwa masalah yang muncul akibat ketidakjelasan status tanah pasca berakhirnya izin HGU tersebut.  dari pandangan aturan hukumya sudah dengan sangat terang bahwa tanah yang sudah habis masa HGUnya menjadi kewajiban PTPN XIV untuk mengembalikannya kepada negara sebagai pihak yang memberikan izin. Perbaikan rantai perizinan perkebunan dimulai dari izin lokasi, izin pelepasan Kawasan hutan, izin usaha perkebunan, izin perkebunan budidaya, izin usaha perkebunan pengelolahan, izin land clearing.Kata Kunci : Hak Guna Usaha, Perizinan, Perkebunan.